Dual ontogeny of disease-associated microglia and disease inflammatory macrophages in aging and neurodegeneration - Silvin, Aymeric; Uderhardt, Stefan; Piot, Cecile; Da Mesquita, Sandro; Yang, Katharine; Geirsdottir, Laufey; Mulder, Kevin; Eyal, David; Liu, Zhaoyuan; Bridlance, Cecile; Thion, Morgane Sonia; Zhang, Xiao Meng; et al. (Immunity, 2022)
Brain macrophage populations include parenchymal microglia, border-associated macrophages, and recruited monocyte-derived cells; together, they control brain development and homeostasis but are also implicated in aging pathogenesis and neurodegeneration. The phenotypes, localization, and functions of each population in different contexts have yet to be resolved. We generated a murine brain myeloid scRNA-seq integration to systematically delineate brain macrophage populations. We show that the previously identified disease-associated microglia (DAM) population detected in murine Alzheimer's disease models actually comprises two ontogenetically and functionally distinct cell lineages: embryonically derived triggering receptor expressed on myeloid cells 2 (TREM2)-dependent DAM expressing a neuroprotective signature and monocyte-derived TREM2-expressing disease inflammatory macrophages (DIMs) accumulating in the brain during aging. These two distinct populations appear to also be conserved in the human brain. Herein, we generate an ontogeny-resolved model of brain myeloid cell heterogeneity in development, homeostasis, and disease and identify cellular targets for the treatment of neurodegeneration.
CRIS-Team Scopus Importer:2022-09-02
Keywords: aging; Alzheimer's disease; disease inflammatory macrophages; disease-associated microglia; macrophage; microglia; neurodegeneration